Likya Yolu’nu Yürüyen Turistlerin Seyahat Motivasyonları ve Memnuniyet Düzeyleri(Travel Motivations and the Satisfaction Levels of the Tourists Walking the Lycian Way) - Yılmaz AKGÜNDÜZ; Gaye KIZILCALIOĞLU (Yönetim ve Ekonomi, 2016)
This study aims to determine the demographics, travel motivations, general satisfaction levels and future behavioral intentions of the tourists walking The Lycian Way. The data collected in the scope of the study were obtained from the tourists who walked in The Lycian Way in the MarchApril 2014 period by using the convenience sampling method with the questionnaires. The questionnaires were designed to determine the travel motivations, satisfaction levels and demographic characteristics of the tourists in three parts each of which containing expressions to define the abovementioned properties. At the end of the field study, 407 valid questionnaires were attained. As a result of the correlation and regression analyses; performed to test the hypothesis, it has been determined that the travel motivations of the tourists walking in The Lycian Way could be examined under the titles such as socializing and self-realization, traveling independently, knowing the world, searching for experience and quietness. It has also been determined that socializing and self-realization motivation affects the general satisfaction level positively. It has been observed that the general satisfaction level has a negative effect on the intention of revisiting the same place and on the intention of recommending it to other people.